Synthesis and structural identification of 3,6-Bis(3,5- dimethylpyrazol-1-yl)-1,2,4,5-tetrazine (BDT) - Hoang Trung Huu; Nguyen Van Dung; Ha Dinh Viet (Journal of Military Science and Technology, 2024)
3,6-Bis(3,5-dimethylpyrazol-1-yl)-1,2,4,5-tetrazine (BDT) has emerged as a key intermediate for accessing other promising tetrazine-based high-energy-density compounds. The study presented the step-by-step process of synthesizing BDT while thoroughly analyzing and investigating its crystal structure. The chemical structure of BDT was characterized using spectroscopic techniques such as FT-IR, 1H-NMR, 13C-NMR, and data from PXRD and CCDC 254069. BDT was analyzed using various theoretical techniques, such as 2D fingerprint and Hirshfeld surface. The morphology of the BDT crystals was evaluated through optical microscope images. The results show that BDT crystallizes in a monoclinic space group P21/c, with four molecules per unit cell (Z=4) with the calculated lattice parameters as follows: a = 11.37 Å, b = 16.67 Å, c = 7.74 Å. The proportion of interactions of N...H and H...H of the total Hirshfeld surface area of BDT were 31.9% and 45.7%, respectively. ESP’s maximum negative and positive values are -212.9 kJ.mol-1 and 65.6 kJ.mol-1, respectively.